2017
DOI: 10.3389/fnagi.2017.00389
|View full text |Cite|
|
Sign up to set email alerts
|

Behavioral and Neuroimaging Evidence for Facial Emotion Recognition in Elderly Korean Adults with Mild Cognitive Impairment, Alzheimer’s Disease, and Frontotemporal Dementia

Abstract: Background: Facial emotion recognition (FER) is impaired in individuals with frontotemporal dementia (FTD) and Alzheimer’s disease (AD) when compared to healthy older adults. Since deficits in emotion recognition are closely related to caregiver burden or social interactions, researchers have fundamental interest in FER performance in patients with dementia.Purpose: The purpose of this study was to identify the performance profiles of six facial emotions (i.e., fear, anger, disgust, sadness, surprise, and happ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 103 publications
2
48
0
Order By: Relevance
“…Failures of ToM refer to difficulties understanding the mental states of others and appreciating that these mental states might differ from our own (Poletti et al, 2012). In AD, these social cognitive deficits have been linked to both volumetric loss and white matter pathology (Dermody et al, 2016;Guntekin et al, 2019;Kanske et al, 2015;Lee et al, 2013;Park et al, 2017;Poletti et al, 2012;Sturm et al, 2013). Consequently, it is unsurprising that both types of impairment grow more severe with disease progression (Fliss et al, 2016;Kumfor et al, 2014;Sturm et al, 2013;Torres et al, 2015).…”
mentioning
confidence: 99%
“…Failures of ToM refer to difficulties understanding the mental states of others and appreciating that these mental states might differ from our own (Poletti et al, 2012). In AD, these social cognitive deficits have been linked to both volumetric loss and white matter pathology (Dermody et al, 2016;Guntekin et al, 2019;Kanske et al, 2015;Lee et al, 2013;Park et al, 2017;Poletti et al, 2012;Sturm et al, 2013). Consequently, it is unsurprising that both types of impairment grow more severe with disease progression (Fliss et al, 2016;Kumfor et al, 2014;Sturm et al, 2013;Torres et al, 2015).…”
mentioning
confidence: 99%
“…In a quantitative MRI study, a direct correlation has been found between temporal volume and low score in negative facial expression recognition. However, while previous reports agree with the observation that negative emotions are poorly recognized in AD and PD, conflicting results have been obtained when searching for a specific emotion (39,40). Most studies on facial expression recognition have been made using a static image presentation, which is a less naturalistic and less-sensitive approach.…”
Section: Discussionmentioning
confidence: 92%
“… The facial stimuli representing the six basic emotions and the neutral emotion, adapted from [ 60 ]. …”
Section: Figurementioning
confidence: 99%